Euthanasia and palliative care problems in the views of sixth year medical students - Leppert, Wojciech; Gottwald, Leszek; Kaźmierczak-Łukaszewicz, Sylwia (Medycyna Paliatywna/Palliative Medicine, 2009)
Background: Ethical problems in the care of patients with advanced diseases are important elements of palliative medicine. Aim of the study: To determine medical students’ knowledge of definitions of euthanasia and physician-assisted suicide (PAS) as well as their views on the practice of euthanasia and its legalization. Material and methods: A questionnaire survey of 263 sixth year medical students of Poznan and Lodz Medical Universities was carried out after obligatory palliative medicine classes. Students were provided with basic knowledge on symptom treatment, psychological, social and spiritual support, and basic ethics; palliative care was presented as opposed to euthanasia and PAS. The survey was voluntary and anonymous. Results: Respondents were aged 23-33 (mean 24.64). Among 224 (85.34%) who stated their religion there were 220 (98.21%) Catholics, and 4 (1.79%) of other religions (p < 0.001). Euthanasia and PAS definitions were both recognized by 204 (77.57%), one by 41 (15.59%), and neither by 18 (6.84%) respondents (p < 0.001). 152 respondents would not practise euthanasia or PAS (57.79%), 36 would practise them (13.69%), and 75 could not answer (28.52%) (p < 0.001); differences between universities were significant (p < 0.001). In the case of one’s own or a relative’s incurable disease, 163 respondents would choose natural death (61.98%), 45 euthanasia (17.11%), and 65 PAS (20.91%) (p < 0.001); differences between universities were significant (p < 0.02). 92 students supported euthanasia or PAS legalization (34.98%), 129 opposed it (49.05%), and 42 could not respond (15.97%) (p < 0.001); there were no differences between universities. Conclusions: Most students were in opposition to euthanasia practice and legalization; more respondents support euthanasia legalization. A significant percentage of respondents could not answer the questions.